Antimicrobial activity of different filling pastes for deciduous tooth treatment - Bruna Feltrin ANTONIAZZI; Carine Weber PIRES; Carmela Rampazzo BRESOLIN; Rita Niederauer WEISS; Juliana Rodrigues PRAETZEL (Sociedade Brasileira de Pesquisa Odontológica, 2015)
Guedes-Pinto paste is the filling material most employed in Brazil for endodontic treatment of deciduous teeth; however, the Rifocort® ointment has been removed. Thus, the aim of this study was to investigate the antimicrobial potential of filling pastes, by proposing three new pharmacological associations to replace Rifocort® ointment with drugs of already established antimicrobial power: Nebacetin® ointment, 2% Chlorhexidine Gluconate gel, and Maxitrol® ointment. A paste composed of Iodoform, Rifocort® ointment and Camphorated Paramonochlorophenol (CPC) was employed as the gold standard (G1). The other associations were: Iodoform, Nebacetin® ointment and CPC (G2); Iodoform, 2% Chlorhexidine Digluconate gel and CPC (G3); Iodoform, Maxitrol® ointment and CPC (G4). The associations were tested for Staphylococcus aureus (S. aureus), Streptococcus mutans (S. mutans), Streptococcus oralis (S. oralis), Enterococcus faecalis (E. faecalis), Escherichia coli (E. coli), and Bacillus subtilis (B. subtilis), using the methods of dilution on solid medium - orifice agar - and broth dilution. The results were tested using statistical analysis ANOVA and Kruskal-Wallis. They showed that all the pastes had a bacteriostatic effect on all the microorganisms, without any statistically significant difference, compared with G1. S. aureus was statistically significant (multiple comparison test of Tukey), insofar as G2 and G3 presented the worst and the best performance, respectively. All associations were bactericidal for E. coli, S. aureus, S. mutans and S. oralis. Only G3 and G4 were bactericidal for E. faecalis, whereas no product was bactericidal for B. subtilis. Thus, the tested pastes have antimicrobial potential and have proved acceptable for endodontic treatment of primary teeth.